Foraging depth depicts resource partitioning and contamination level in a pelagic shark assemblage: Insights from mercury stable isotopes. (15th August 2021) - Besnard, Lucien; Le Croizier, Gaël; Galván-Magaña, Felipe; Point, David; Kraffe, Edouard; Ketchum, James; Martinez Rincon, Raul Octavio; Schaal, Gauthier
Abstract: The decline of shark populations in the world ocean is affecting ecosystem structure and function in an unpredictable way and new ecological information is today needed to better understand the role of sharks in their habitats. In particular, the characterization of foraging patterns is crucial to understand and foresee the evolution of dynamics between sharks and their prey. Many shark species use the mesopelagic area as a major foraging ground but the degree to which different pelagic sharks rely on this habitat remains overlooked. In order to depict the vertical dimension of their trophic ecology, we used mercury stable isotopes in the muscle of three pelagic shark species (the blue shark Prionace glauca, the shortfin mako shark Isurus oxyrinchus and the smooth hammerhead shark Sphyrna zygaena ) from the northeastern Pacific region. The Δ 199 Hg values, ranging from 1.40 to 2.13‰ in sharks, suggested a diet mostly based on mesopelagic prey in oceanic habitats. We additionally used carbon and nitrogen stable isotopes (δ 13 C, δ 15 N) alone or in combination with Δ 199 Hg values, to assess resource partitioning between the three shark species. Adding Δ 199 Hg resulted in a decrease in trophic overlap estimates compared to those based on δ 13 C/δ 15 N alone, demonstrating that multi-isotope modeling is needed for accurate trophic description of the three species. Mainly, it reveals that they forage at different average depths and that resource partitioning is mostly expressed through the vertical dimension within pelagic shark assemblages. Concomitantly, muscle total mercury concentration (THg) differed between species and increased with feeding depth. Overall, this study highlights the key role of the mesopelagic zone for shark species foraging among important depth gradients and reports new ecological information on trophic competition using mercury isotopes. It also suggests that foraging depth may play a pivotal role in the differences between muscle THg from co-occurring high trophic level shark species. Graphical abstract: Image 1 Highlights: δ 13 C, δ 15 N, Δ 199 Hg and δ 202 Hg were determined in three pelagic shark species. Hg isotopes suggest that these shark species forage on mesopelagic prey. δ 13 C and δ 15 N overestimate overlaps between trophic niches. Differences in foraging depth better explain resource partitioning. Foraging depth influences mercury contamination level. Abstract : By analyzing the isotopic ratios of mercury, a major pollutant in marine ecosystems, this study characterized the foraging depth of three shark species. Feeding depth governed resource partitioning between species and explained mercury concentration in sharks.